Public Emotions
XI, 254 p.
Keywords: Emotions are central to our practices and understanding of public life. This book examines the political, social and personal consequences of public emotions in relation to conflict, ritual, social classification, collective life, identity, memory and power and is a multidisciplinary collaboration showing the emotional character of public life.